Suppose the integral solutions of the equation : x 3 + 1 0 x − 1 = y 3 + 6 y 2 are
( x 1 , y 1 ) , … , ( x n , y n ) .
Find the value of ( x 1 + y 1 ) + … + ( x n + y n ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution, understandable and intuitive.
H o w d o w e t r y 0 ≤ x − y ≤ 6 a n d w h y t h e r e c o u l d n o t b e m o r e p a i r s ? x = − 1 0 0 , y = − 1 0 1 s a t i s f i e s 0 ≤ x − y ≤ 6 . s o a l s o x = 1 0 1 , y = 1 0 0 .
We may program on spread-sheet, calculator, or a computer language:- I n i t i a l B = C = 1 0 0 O u t e r D o l o o p A = − 1 0 0 , 1 , 1 0 0 I n n e r D o L o o p x = − 1 0 0 , 1 , 1 0 0 C = B B = A + 6 x 3 + 1 0 x − 1 − A 2 I f B = 0 P r i n t x a n d A I f C ∗ B ≤ 0 e n d i n n e r l o o p g o t o n e x t f o r o u t t e r l o o p . For calculator with the help of ENTRY in TI calculators, and STO things like Printing, ending loop, going to next, If, all are manual. We remain satisfied investigating between -100 and 100!!.
Problem Loading...
Note Loading...
Set Loading...
y 2 term on the RHS of the equation tells us that y can not be greater than x . We'll find out that, let x − y = z ( y + z ) 3 + 1 0 ( y + z ) − 1 = y 3 + 6 y 2 ( 3 z − 6 ) y 2 + ( 3 z 2 + 1 0 ) y + z 3 + 1 0 z − 1 = 0 Discriminant of the obtained quadratic (in terms of y ) must be non-negative (why?) ( 3 z 2 + 1 0 ) 2 − 4 ( 3 z − 6 ) ( z 3 + 1 0 z − 1 ) ≥ 0 0 ≤ z ≤ 6 Trying these values gives y = 5 for z = 1 and y = − 3 for z = 5 only. So totally two pairs ( x , y ) = ( 6 , 5 ) , ( 2 , − 3 )